Nanostructured Bifunctional Hydrogels as Potential Instructing Platform for Hematopoietic Stem Cell Differentiation - Kratzer, Domenic; Ludwig-Husemann, Anita; Junges, Katharina; Geckle, Udo; Lee-Thedieck, Cornelia (Frontiers in Materials, 2019)
Hematopoietic stem cells (HSCs) are blood forming cells which possess the ability to differentiate into all types of blood cells. T cells are one important cell type HSCs can differentiate into, via corresponding progenitor cells. T cells are part of the adaptive immune system as they mediate cellular immune responses. Due to this crucial function, in vitro differentiated T cells are subject of current studies in the biomedical field in terms of cell transplantation. Studies show that the density of the immobilized Notch ligand Delta-like 1 (DLL1) presented in HSCs´ environment can stimulate their differentiation toward T cells. The development of reliable synthetic cell culture systems presenting variable densities of DLL1 is promising for the future expansion of T cells´ clinical applications. Here we introduce bifunctional polyethylene glycol-based (PEG-based) hydrogels as potential instructing platform for the differentiation of human hematopoietic stem and progenitor cells (HSPCs) to T cells. PEG hydrogels bearing the cell adhesion supporting motif RGD (arginyl-glycyl-aspartic acid) were synthesized by UV-light induced radical copolymerization of PEG diacrylate and RGD modified PEG acrylate. The hydrogels were furthermore nanostructured by incorporation of gold nanoparticle arrays that were produced by block copolymer micelle nanolithography (BCML). BCML allows for the decoration of surfaces with gold nanoparticles in a hexagonal manner with well-defined interparticle distances. To determine the impact of DLL1 density on the cell differentiation, hydrogels with particle distances of approximately 40 nm and 90 nm were synthesized and the gold nanoparticles were functionalized with DLL1. After 27 days in culture, HSPCs showed an unphysiological differentiation status and, therefore, the differentiation was evaluated as atypical T lymphoid differentiation. Cluster of differentiation (CD) 4 was the only tested T cell marker which was expressed clearly in all samples. Thus, although the applied nanopatterned hydrogels affected two important signaling pathways (integrins and Notch) for T cell differentiation, it appears that more functionalities that control T cell differentiation in nature need to be considered for achieving fully synthetic in vitro T cell differentiation strategies.